Invisible borders in educational technology research? A comparative analysis - Marín, Victoria I.; Buntins, Katja; Bedenlier, Svenja; Bond, Melissa (Educational Technology Research and Development, 2023)
Educational research is reflective of the nature and structure of national and regional education systems and their historical evolution. Educational technology research, as an area within educational research, reflects this case particularly prominently. Although individual countries and regions have varying research traditions, the publication of research in English as the scientific lingua franca can lead to missing nuances in terminology, which is often not reflected upon. Despite this, the exploration of research from different countries can still uncover diverse topical clusters. This study aims to identify the research topics in educational technology research in three countries (Germany, Spain and the United Kingdom), each with their own research traditions, through the terms used. To this end, a bibliometric analysis of 3034 article abstracts and keywords from 29 English-language Web of Science journals in the field of education and educational research was conducted, with a focus on educational technology. In addition, the quantitative findings are comparatively analysed by considering the corresponding cultural clusters. Main findings include diverse research foci in the three countries, also showing that distinct research traditions are still present, despite using English as lingua franca. Therefore, research articles written in English by non-English authors often do not reflect the same meanings in each country, despite using the same words. The conclusions reflect upon the need to establish ways of understanding the traditions behind those research articles and build collaborative systems to illustrate nuances in this research.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Bibliometric analysis; Comparative research; Educational research traditions; Educational technology research